Digital Mastery in the Population and Civil Registration Office of Depok City: Toward Government Digital Transformation - Nadya Azzira Farenica; Dahyar Daraba; Tri Raharjanto (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Digital transformation in public service delivery has driven the implementation of the Digital Population Identity (Identitas Kependudukan Digital/IKD) as part of the Electronic-Based Government System (Sistem Pemerintahan Berbasis Elektronik/SPBE) to enhance efficiency and integration of population administration based on the National Identification Number (NIK). However, the implementation of IKD at the Department of Population and Civil Registration of Depok City still faces several challenges, including low activation rates, limited public literacy and trust, the proliferation of fraud conducted under the guise of IKD, and the internal readiness of the bureaucracy to manage digital transformation. This study aims to analyze the level of readiness and digital mastery of the Department of Population and Civil Registration of Depok City and to identify strategic aspects that need to be strengthened to support the successful digital transformation of population administration services. The Digital Mastery theory proposed by Westerman, Bonnet, and McAfee (2014) is employed as the primary analytical framework to understand and assess the processes and levels of digital mastery within the research context. The theory emphasizes that successful digital transformation is determined by a balance between digital capabilities and leadership capabilities. The combination of these two dimensions results in four levels of digital mastery, namely Beginners, Fashionistas, Conservatives, and Digital Masters. This study adopts a qualitative descriptive method with an inductive approach. The findings indicate that the digital mastery of the Department of Population and Civil Registration of Depok City in supporting government digital transformation through the activation of Digital Population Identity (IKD) is positioned at the Conservative level within the Digital Mastery framework of Westerman et al. (2014). This level is characterized by the availability of stable, secure, and standardized digital systems and a focus on the use of technology to improve administrative efficiency. Although leadership commitment to digitalization is evident through support for IKD implementation, regulatory compliance, and personal data protection, the utilization of technology and digital leadership remains operational and risk-control oriented. As a result, it has not fully driven service innovation, strategic data utilization, or enhanced user experience. Therefore, advancing digital mastery toward the Digital Master level requires strengthening an integrated digital strategy between central and local governments, developing visionary digital leadership, enhancing the digital competencies and culture of public officials, improving public digital literacy and trust, and fostering sustained synergy with the Directorate General of Population and Civil Registration to promote citizen-oriented digital transformation in population administration services.